SYNTHESIS AND CHARACTERIZATION OF NEW N-TERMINAL BCHAIN MODIFIED HUMAN INSULIN ANALOGUES - Shneine, Jewad K (Al-Nahrain Journal of Science, 2010)
New human insulin analogues were synthesized by fragment condensation reactions of N A1,N B29 Msc protected native human insulin of different B-chain lengths with the dipeptide Boc-Asn-Thr-OH. Edman degradation was used to obtain shortened B-chain insulin intermediates.Purification of the products was achieved using gel filtration, ion exchange chromatography andRP-MPLC chromatography. Analysis of synthesized analogues accomplished by RP-HPLCchromatography and amino acid analysis. The modified insulin analogues with the amino acidsAsparagine in the first position and Threonine in the second position of the N-terminal B-chain ofinsulin would be expected to show an enhanced T R* transition compared with that of wild-typestructure.